A mini-review of track and field`s talent-identification models in iran and some designated countries - Mirkolaee, E. G.; Razavi, S. M. H.; Amirnejad, S. (Annals of Applied Sport Science, 2013)
Talent identification and training the athletes of the basic levels in track and field requires codifying a proper model like any other system so that any duplication is prevented as well as knowing the right path. The federation of track and field started to codify the national talent-identification scheme in track and field in 2006. Hence, the present studies track-and-field talent-identification patterns in some designated countries and compare them with the codified pattern in Iran. The research method of the present survey is of review which studies track-and-field talent-identification patterns in countries like the Russia (Soviet Union), the Germany (former East Germany), China, Australia, Romania, Italy, USA, England, Hungary, Canada, Japan, Qatar, Malaysia, and Iran. Studying track-and-field talentidentification pattern in Iran shows that lack of a new opportunity for trainees and unsustainability of the practical talent-identification scheme have been of its setbacks. Also, comparing the patterns shows that the most important principle of talent-identification scheme in designated countries are cooperation with the institutional sport, continuity of the talent-identification scheme, and supporting and training the elite athletes to help them reach the championship.